Participation in Budgeting, Locus of Control and Organizational Effectiveness. - Brownell, Peter (The Accounting Review, 1981)
ABSTRACT: This study examines the role of the personality variable, locus of control, as a moderator of the relationship between budgetary participation and managerial performance. The results of a laboratory study employing two separate subject groups–undergraduate accounting students and managers from a large manufacturing company–show a statistically significant interaction between participation and locus of control affecting performance. Budgetary participation was found to have a positive effect on individuals who feel they have a large degree of control over their destiny ("internals" on the locus of control scale), while having a negative effect on those individuals who feel that their destinies are controlled by luck, chance, or fate ("externals" on the locus of control scale). The results are discussed and possible applications in the areas of job redesign and personnel selection and placement are considered.